Risk Perception during Information System Development in Non-Profit Health Care Organizations - Vimarlund, V.; Timpka, T.; Ljunggren, M. (Methods of Information in Medicine, 1998)
The perception of risk exposure among design team members during the early phases of information system development projects can provide valuable strategic information for clinical organizations. To develop a typology of perceived risks during information system development projects in health care, interviews were performed with key team members from a specialist clinic, primary health care, and an informatics research group, during the requirements specification. Phenomenological data analysis and secondary integration of the results in available theories were performed. System objectives, the user requirements definition procedure, the communication pattern between design team members and project management were found to be perceived as the main risk areas. In the secondary analysis, the technical factors, identified as preventing a maximization of the use of the resources, were lack of informatics knowledge among economic decision makers and differences between customers and suppliers regarding their views on the nature of system design. During the implementation of a given strategy, decision makers may consider the requests of their own sponsors in the first place and maximize the use ofthe project resources in the second place. Informatics knowledge plays a key role in risk perception during the development of an information system in health care. Political considerations by team members are important to take into regard, since these may influence technical and economic decisions.
Keywords: Risk Perception; Health-Care Organizations; Phenomenological Analysis; Informatics Knowledge; Political Considerations; Technical and Economic Factors